Child/youth work and school learning: complex relations (Praxis Educativa, 2012)
The aim of this paper is to share some similarities about what children and young people obtain from work and school. The main protagonists in the research are children and young people who try to cope with two activities: school learning and work. The objective of this paper is twofold: on the one hand, to make visible child and adolescent work in our region, since there is not a symbolic or social re-cognition of it, neither from the school sector nor from people in general and, on the other hand, to show that the school/work relation is a complex one: working children have to deal with different situations in order to keep up schooling: absences, late arrivals, tiredness, temporary desertion, promotion failure, lack of time to study and do homework. These students do not get special attention from their families, the state or the school system.
Keywords: family; school; child work; agency; make visible